(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2022)
This article proposes to share, socialize and reflect the challenge of university extension in the Faculty of Human Sciences of the National University of Río Cuarto, Argentina, which in 2020 acquires very particular nuances facing the pandemic caused by Covid-19. The restrictions of isolation and social distancing imposed new institutional conditions in the work of knowing, listening, guiding, managing or trying to solve problems that arose with the pandemic. To address this issue, a record, systematization and analysis of the proposals that emerged at the time were carried out in order to characterize the extension scenario, some regulations and main actions, in this context. In an introductory way, a brief tour that has been taking place around a process of strengthening the extension in the Faculty of Human Sciences is recovered commenting on some outstanding points that provide the basis for the redefinition of frameworks for action and new activities undertaken, placing the potential of extension as a strategic space to promote encounters between teaching and research, relations between University and Society and the development of proposals in the face of the various situations demanded by structural inequalities and visible violation processes in the socio-territorial space. The context of the pandemic and its effects makes it possible to demonstrate some adaptations that were assumed from the management of university extension; the generation of new devices as an entry channel for initiatives of the extension teams, the reorientation of objectives and priority lines and the combination of face-to-face and virtual activities, among other aspects. The training and communication activities may account of the accompaniment that was promoted